An Interactive Program for Shape Optimization of Sections Under Saint-Venant Torsion Using Boundary Element Method - Berkowski, P.; Sieczkowski, J.M.; Doblaré, M.; Garcia, L. (Engineering Transactions, 1995)
An interactive program for visualization of results generated during the shape optimization of simply and multiply-connected isotropic sections under the Saint-Venant torsion using B.E.M. is presented in this paper. The program includes some graphical tools essential for preprocessing, analysis and postprocessing parts of the optimization system and makes it possible to carry out boundary mesh modifications caused by changes in its geometry and initial mesh, and also by the intersecting boundaries. In order to show the influence of the geometric irregularities and intersections of the boundaries on the optimization process as well as the advantages of the program proposed, some examples of the shape optimization are presented.